Development Of The Readability Index Model For Young Adults With Reading Difficulties In Malay Language - Mohamad Hazawawi, Nur Amalina (2019)
Recent studies reported different perspectives of the relationship among human, technology and education. Reading is a fundamental part of language competency. The motivation of this study is based on the fact that there are some young adults aged 18 years old and above who still cannot read properly and are having difficulties in reading and writing. Due to the unavailability of a tool that can measures the readability levels of Malay texts, this study proposed an online readability test tool in the Malay language to include readers who have reading difficulties by using an existing conventional calculation method developed by the Malay linguists. This formula was then transformed into a computing algorithm to detect the difficult words in Malay texts. This online tool is known as Sistem Penilaian Kebolehbacaan Bahasa Melayu (SPIKE) aims to measure the readability levels of Malay reading materials and to focus on detecting difficult Malay words. SPICE (Software Process Improvement and Capability Determination) had been chosen as research methodology, where consists of five main ideas which are S(Situation), P(Problem), I(Investigate), C (Construct) and E(Evaluate). SPIKE is part of a continuous work done to evaluate the reading competencies among young adults with dyslexia. From the existing readability formula and recent studies, a new parameter, which is the potential difficult word was found to help the dyslexics, especially in reading. The findings reported that the additional parameters like words that have more than three syllables and potential difficult words influenced the time taken in reading the assessment. This tool will increase the accuracies in measuring reading competencies among young adults, and will be able to help the dyslexic users with reading difficulties in knowing the level of readability of each reading materials.